Learning Cycle 7E Learning Model: Optimizing Student Learning Outcomes in Aqidah Akhlak - Rosa Shafira Ulya; Erlina Erlina; Sunarto Sunarto (ETDC: Indonesian Journal of Research and Educational Review, 2026)
This research focuses on MA Nurul Iman Sekincau's low student learning results in the evaluative and creative parts of Aqidah Akhlak. Low student participation and traditional learning paradigms may hamper higher-order thinking. This quantitative study tests the 7E Learning Cycle model's impact on student learning, particularly at cognitive levels C5 (evaluating) and C6 (creating), as well as affective and psychomotor domains. The study was quasi-experimental with a post-test-only control group. A was the experimental group that received the 7E Learning Cycle model, while B was the control group that used conventional methods. Multiple-choice cognitive C5 and C6 exams, self-assessment questionnaires, and performance observation sheets were used. The findings of the data analysis demonstrated that the 7E Learning Cycle model considerably improved student learning. Cognitive hypothesis testing revealed a significant difference between experimental and control groups (t-value = 3.581, p < 0.001). Through internalizing character ideals and religious attitudes, this model significantly impacted the affective and psychomotor domains (p = 0.000, mean difference = 3.721), outperforming the control group. The cognitive instrument had critical notes since it was dominated by easy and very easy items (86.66%), so its discriminatory power needed to be increased despite meeting validity and reliability requirements. This study found that the 7E Learning Cycle model can help Madrasah educators improve Aqidah Akhlak learning through active involvement and high-level cognitive stimulation.